"Proporz JA // Sie muss kommen die Wahlgerechtigkeit" - Bauer und Junge mit Laterne
politischer Rahmen;Wahlen und Abstimmungen;Wahl;Wahlsystem;Proporzwahl politischer Rahmen;Wahlen und Abstimmungen;Volksabstimmung